The Research–Teaching Nexus in Politics and International Relations in the UK: A Survey of Practices and Attitudes. (February 2015) - Lightfoot, Simon; Piotukh, Volha
This article discusses the results of a small-N survey of established academic staff within the discipline of politics and international relations and how they view research–teaching links. It reveals that even among this small group there are very different views as to the relationship between teaching and research. The article argues that more work is needed to produce a fuller understanding of the nexus across the discipline and that research needs to be integrated at all levels of undergraduate study. Fundamentally, we need to make the link explicit to both students and other stakeholders to ensure that the nexus remains viable in the future.